2023
DOI: 10.1088/1748-605x/acd318
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol loaded native silk fiber-sericin hydrogel double interpenetrating bioactive wound dressing facilitates full-thickness skin wound healing

Abstract: Wound repair is challenging for traditional wound dressings. New bioactive dressings need to be developed urgently. Herein, we reported a highly bioactive silk protein wound dressing (SPD) with natural silk fiber-sericin hydrogel interpenetrating double network structure, which combines the dual characteristics of natural silk and sericin hydrogel. Silk fiber scaffolds were secreted directly from silkworms bred by regulating their spinning behaviors. Sericin in SPD is obtained by dissolving silkworm cocoons at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Li et al reported the development of a natural silk fibroin-gelatin hydrogel-based dressing loaded with resveratrol, which was subsequently employed for wound healing applications. 152 Yu and colleagues formulated a CMCS-plantamajoside hydrogel comprising plantamajoside, a natural Chinese herbal medicine known for its antioxidation capabilities. This hydrogel effectively diminished oxidative stress indicators and exhibited enhanced wound healing, as evaluated through an in vivo burn wound model.…”
Section: Multiple Functions Of Hydrogel-based Dressingsmentioning
confidence: 99%
“…Li et al reported the development of a natural silk fibroin-gelatin hydrogel-based dressing loaded with resveratrol, which was subsequently employed for wound healing applications. 152 Yu and colleagues formulated a CMCS-plantamajoside hydrogel comprising plantamajoside, a natural Chinese herbal medicine known for its antioxidation capabilities. This hydrogel effectively diminished oxidative stress indicators and exhibited enhanced wound healing, as evaluated through an in vivo burn wound model.…”
Section: Multiple Functions Of Hydrogel-based Dressingsmentioning
confidence: 99%
“…In recent years, wound healing patches containing sericin have been the center of attention (Table 2). Sericin as a component of the matrix appeared next to polymers: poly (vinyl alcohol) [236], sodium carboxy-methyl-cellulose and polyvinyl alcohol [237], placentaderived extracellular matrix [238], silk fiber [239], PVA/chitosan [240], PVA [241], robust alcohol, polyurethane/chitosan [242], carboxymethyl cellulose [243], poly (N-isopropylacrylamide) [244], cellulose/silk nonwoven fabric [245], collagen-fibrin [246], poly(2-hydroxyethyl methacrylate) [247], cellulose [248], carboxymethyl cellulose as hydrogels [249], cellulose/poly(vinyl alcohol) [250], poly lactide-co-glycolic acid [251], PVA/collagen [252], PVA/chitosan [253], polycaprolactone/cellulose acetate/fibroin [254], poly(ethyleneterephhalate)-g-poly (hydroxyethylmethacrylate, PET-g-HEMA) nanofibers [255], sericin/chitosan/polyvinyl alcohol [256], gelatin [257], fibroin [258], poly(Σ-caprolactone)/poly(ethylene oxide) [259]. There are also sericin-based patches with only sericin or sericin treated with HRP/H 2 O 2 as a matrix, but in significantly smaller amounts [260,261].…”
Section: State Of Innovation In Sericin-polymer Wound Healing Patchesmentioning
confidence: 99%
“…There are also sericin-based patches with only sericin or sericin treated with HRP/H 2 O 2 as a matrix, but in significantly smaller amounts [260,261]. The main active substances in those inventions included resveratrol [239], turmeric [243], silver nanoparticles [255], poly(lactic-co-glycolic acid) nanoparticles [257], and sericin as a sole ingredient [260,261] or in combinations with human placenta [238], silver [244], collagen [246] or azithromycin [250]. The applications of sericin-polymer patches in recent years involved wound treatment [238,239,[243][244][245]249,250,252,254,257,259,261], including acute [237] and infected large burn wounds [236], artificial skin [242], wound dressings [240,241,248,253,255,258], tissue engineering [247], regenerative scaffolds [246], and periodontal tissue engineering [251].…”
Section: State Of Innovation In Sericin-polymer Wound Healing Patchesmentioning
confidence: 99%
“…At present, sericin has been employed to fabricate various bioactive polymers [27,[31][32][33], and preliminary studies have been conducted in the repair of injured skin [27], muscle [29], nerve [34,35], and others. The combination of the merits of sericin with the properties of hydrogels endows the biomaterial with excellent histocompatibility and the capability of creating a moderately moist microenvironment for wounds [36]. Moreover, the porous structure of hydrogel facilitates the loading of cells, drugs, or other biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%